DEMOCRACY IN DIGITAL TIMES: THE INFLUENCE OF NEW SOCIAL MEDIA ON YOUTH POLITICAL SOCIALIZATION AND THE IMPORTANCE OF MEDIA LITERACY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes the strategic role of media and information literacy in combating hate speech, fake news, and misinformation in the digital environment. It begins by contextualizing the socialization and political culture of contemporary youth, with an emphasis on the impacts of new social media in this formative process. Next, it discusses the role of traditional media and digital platforms in the post-truth era, highlighting the influence of algorithmic personalization, ideological polarization, and misinformation on the construction of public opinion. Media and information literacy is presented as the development of critical, ethical, and responsible competencies in the use of technologies and in the consumption and production of informational content. Finally, it is argued that strengthening public policies and pedagogical practices focused on media and information literacy is essential to forming more conscious, resilient, and engaged citizens, thereby contributing to a safer, more plural, and democratic internet.